Faktor-Faktor Yang Mempengaruhi Turnover Intention Dengan Variabel Intervening Kepuasan Kerja Dan Komitmen Organisasi - Ni Luh Wulani Parwati; Ida Bagus Raka Suardana (Jurnal Manajemen dan Bisnis, 2015)
Arranging employee is a difficult and complex matter because they have differentmind, feeling, status, will and background bring to company so employee can not be set andcharged as like setting machine, capital, building, etc. So this indicates that the need toconduct effective human resources management in organization.Sample determination technique is maximum likelihood estimation using specificconsideration or criteria is permanent employees, then one become sample on this researchis settled as 138 employees. Method used on this research is Structural Equation Modeling(SEM).Research result indicates that conflict variable of double role has positive andsignificant effect to work stress. Conflict variable of double role to work satisfaction isnegative and significant. Variable of leadership style to stress is negative and significant.Variable of leadership style to work satisfaction is positive and significant. Variable ofleadership style to organization commitment is positive and significant. Variable of workstress to work satisfaction is negative and significant. Variable of work stress to organizationcommitment is negative and significant. Variable of work satisfaction to turnover intention isnegative and significant. Variable of work satisfaction to organization commitment is positiveand significant. Variable of organization commitment to turnover intention is negative andsignificant.Based on the matter so it is expected management can be more attentive also canimproving leadership style and more attention to organization commitment of employees tohotel because can effect work satisfaction. There are several method to use to increaseemployee’s organization commitment to hotel, namely, one of it is by providing adequatefacilities, applying good management to employee’s work system. In addition, can beperformed trying to have outside hotel activities such as outing or rafting in together, so it isexpected can minimize level of employee’s work stress and also turnover intention ofemployee.Keywords: Double role conflict, work stress, leadership style, organization commitment,work satisfaction, and turnover intention.